Go East Java : A Mobile Application For Tourist Guides In East Java - Umi Sa'adah; Imam Mustafa Kamal; Fawaati Tsabita; Vickrilia Yulia Ekaputri (Institut Teknologi Sepuluh Nopember, 2014)
East Java is one province that has many interesting tourism place to visit, both natural and artificial tourism place. However, information about the tourism places is still less spread in the community. Similarly, information related to various tourist facilities around the place like a resort hotel and villas as well as the kind of eating places such as restaurants. Go East Java is a mobile-based application, which will guide tourists in finding the desired tourist spot. In this application, the user is given the choice of natural and artificial tourism areas. For natural menu there are several options: sea, mountains, waterfalls and caves. While on the artificial menu there are options: temple, religion, zoos and parks. After the user specifies the type, it will display a variety of tourism places in East Java, according to the selected category. Each of these sites will be presented in the form of photos, address, phone numbers and its link. In addition, this application also provides information about the various facilities around the tourism place as well as guide maps. In this case the map to the tourism places is presented by offline and online-based on GPS. This application is expected to be increasingly introducing various tourism places in East Java to both domestic and foreign travelers.